Hubungan Pola Konsumsi Zat Besi Dan Konsumsi Suplemen Tablet Besi Dengan Status Anemia Pada Siswi Kelas VIII MTS Negeri Model Martapura Di Wilayah Kerja Dinas Kesehatan Kabupaten Banjar - Yuliana Salman; Rosihan Anwar; Samsul Arifin; STIKES Husada Borneo; Politeknik Kesehatan Banjarmasin; RS Pelita Insani Martapura (HB PRESS, 2014)
Anemia is a condition in which the levels of hemoglobin in the blood is lower than normal according to the threshold values of age and sex. Banjar District Health Office, in January of 2013 doing examination of hemoglobin levels for the second time, from a total of 81 adolescent girls are 22 or 35,8% were affected by anemia and 59 adolescent girls or 64,2% were not anemic. Before examination, adolescent girls given iron suplemen tablet, so many adolescent girls that not anemic. Adolescent girls are prospective students who are candidates for future leaders, prospective workers who will be the backbone of national productivity, as well as the prospective mother will give birth to the next generation and the key to the future care of the child. This study aims to find the relationship of consumption pattern iron and consumption of iron supplements tablet with anemia status at class VIII MTs Negeri Model Martapura working in the District Banjar Health Department. This research uses the analytical method with cross sectional design and was conducted on 81 respondents who had examined levels of hemoglobin by the District Health Office Banjar. Based upon the results of the statistical test using the chi-square indicates that the pattern of consumption of iron obtained p value = 0.04 and consumption of iron supplement tablet obtained p value = 0.00. Its means the relationship between consumption patterns and consumption of iron supplements tablet with anemia status at class VIII MT school girl model work area Martapura in Banjar District Health Department is significant.